Gravidade motora e alterações da marcha de crianças com paralisia cerebral - Marina Barbosa Mendes (2018)
Background: Children and adolescents with cerebral palsy (CP) may present gait kinematics characteristics specifics of CP topography and motor severity. Kinematic deviation may impact individuals functionality, and therefore should be carefully analyzed in order to identify those that contribute positively to the functionality, as well as those that put individuals at risk related to musculoskeletal integrity or compromise the locomotion. The Edinburgh Visual Gait Score (EVGS) is considered the most appropriated instrument to assess gait in clinical environment. Up to date, its not known about major kinematics deviation of children with CP classified in different levels of motor severity, assessed trough EVGS. Aim: To compare the gait kinematics of children and adolescents with Unilateral Spastic Cerebral Palsy (USCP) and Bilateral Spastic Cerebral Palsy (BSCP) classified in different levels of gross motor function, through the observational gait analysis. Methods: A cross-sectional study was carried out with 115 children and adolescents with CP, ages between 4 and 17 years. Fifty-one with USCP, and 65 with BSCP classified in the Gross Motor Function Classification System (GMFCS) in levels I to III, were submitted to EVGS. The main characteristics of gait were extracted through the Principal Components (PC) Analysis, and then, each PC score were compared between GMFCS levels. Results: PC revealed how EVGS items relates to each other to better represent USCP and BSCP gait. Two PC explained 51.3% of the gait variance of children and adolescents with USCP, significant differences were identified in PC1 between GMFCS levels I and II. The PC1 showed movements at the sagittal plane, while PC2 contemplated transverse and frontal planes characteristics. For children and adolescents with BSCP, three PCs explained 53.4% of gait variance, where significant differences were observed in PC2 among children and adolescents classified in GMFCS levels II and III compared to those in GMFCS level I, and in PC3, among children and adolescents with GMFCS levels I and II compared to those with GMFCS level III. PC1 showed mainly ankle and foot segments alterations, while PC2 main characteristics was related to the proximal segments, and PC3 pointed out characteristics related to the preparation and execution of the gait balance phase. Conclusion: This study adds information about the relevance of the observational gait analysis characterizing individuals with spastic CP with different levels of motor severity. This characterization contributes to the intervention process of these children and adolescents, highlighting the relationship between the analyzed body segments of EVGS and each functional group specificities. In addition, this study results may contribute to expanse the use of structured assessment instruments in the clinical environment, such as EVGS.